Stratification of the emergence risk of non communicable diseases associated with the environmental contamination in Cuba - Liliam Cuéllar Luna; Geominia Maldonado Cantillo; Susana Suárez Tamayo; Asela del Puerto Rodríguez; Manuel Romero Placeres (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: The non communicable diseases represent an important sanitary problem at world level, mainly for the developing countries. Objective: To identify the variation of mortality due to lung, breast and prostate cancer   and their possible association with the environmental contamination. Methods: An ecological study at national level was carried out, from 2000 to 2010, taking as analysis unit the municipality. The selected diseases were malignant tumors, specifically those of breast, prostate and lung, and the accumulated typified mortality rates related with these were calculated during this period. Also, the System of Geographical Information was used to make the risk stratification maps, taking as reference the national rate and the main fixed pollutants sources of industrial type were chosen for the analysis of the atmospheric contamination. Results: Maps stratification risk of dying were elaborated for each of the selected diseases and the map of the main fixed pollutants sources of industrial type was obtained; in the same way, other comprehensive maps were elaborated to explore the possible association between these clinical entities and the environmental contamination. Conclusions: The comprehensive analysis of the stratification of the epidemiological and environmental risk reflected that the most affected municipalities were Mariel, Nuevitas and Moa, as well as Matanzas, Cienfuegos, Camagüey and Santiago de Cuba. In Havana the municipalities of Old Havana, Cotorro, San Miguel del Padrón, Arroyo Naranjo, Marianao and Centro Habana stood out.